2018
DOI: 10.1080/14680629.2018.1473286
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of a clayey soil with alkali activated low-calcium fly ash for transport infrastructures applications

Abstract: 19The improvement of geotechnical properties is often achieved by the addition of traditional 20 binders, such as cement or lime. However, the use of such binders implies a considerable 21 financial and environmental cost that needs to be mitigated. An unconventional solution, similar 22 to cement in terms of performance but more environmentally friendly, consists in the use of 23 binders made from alkaline activated industrial residues. The technique consists on the 24 activation of raw materials (such as fly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 23 publications
8
12
0
Order By: Relevance
“…The commercially available software Minitab 17 was used which, based on the number of independent variables assumed, established a total of 13 random runs. The soil/precursor range was defined based on previous experience by the research team (Corrêa- Silva et al, 2019;Cristelo et al, 2018;Miranda et al, 2017;Rios et al, 2016); while the activator/solid range was defined after the maximum and minimum CS content in the paste that presented the most adequate workability. This range was on the 'dry side' of the Proctor curve, thus below the 17% humidity threshold that produced the expansion of the paste.…”
Section: Definition Of the Aac/soil Compositionmentioning
confidence: 99%
“…The commercially available software Minitab 17 was used which, based on the number of independent variables assumed, established a total of 13 random runs. The soil/precursor range was defined based on previous experience by the research team (Corrêa- Silva et al, 2019;Cristelo et al, 2018;Miranda et al, 2017;Rios et al, 2016); while the activator/solid range was defined after the maximum and minimum CS content in the paste that presented the most adequate workability. This range was on the 'dry side' of the Proctor curve, thus below the 17% humidity threshold that produced the expansion of the paste.…”
Section: Definition Of the Aac/soil Compositionmentioning
confidence: 99%
“…The sudden increase in the percentage of Na indicates the possibility of geopolymer gel formation (NASH) [49]. It was proved that low calcium fly ash-based geopolymer results in N-A-S-H formation as a dominant gel, and very low and slower development of calcium silicate hydrate (C-S-H) gel [50]. The decline in the percentages of Si and Al (from point 1 to 3) was mainly a result of the geopolymer reaction with the time elapsed via dissolving alumina and silica, confirming the significant growth in strength [49].…”
Section: Microstructural Analysismentioning
confidence: 99%
“…The latter reaches very significant increases after only 28 days (90 to 95% of its ultimate compressive strength), while alkaline cements based on low-calcium precursors, like the FA used in the present study, have shown significant strength gains even after 90 days [1,14]. The soil used during this research work was already submitted to previous studies that primarily focused on stabilisation with cement and lime, but also with alkaline cements based on FA, aiming at increasing its uniaxial compressive strength (UCS) [2,16]. In short, these studies found that conventional binders reached higher UCS values after 28 days, while the alkaline cements were able to produce higher UCS for longer curing periods, up to 90 days.…”
Section: Introductionmentioning
confidence: 74%
“…However, the rising and ever more acute concerns with the environment have shifted the most important paradigm in the construction industry-the Portland cement dependency-towards the need for more environmentally friendly binders. Alkaline activation is a strong example which, by allowing the introduction of industrial wastes and residues into the fabrication of such alternative binders, represents a twofold advantage, by mitigating the need for OPC and by reducing the volume of wastes that are landfilled [1][2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation